Maria Ramos : transforming Transnet strategy - Nussbaum, Barbara; Mosala, Thabo ([London] : SAGE, 2016)
Transnet is a transport and logistics company controlled by the South African government. Being a government organisation, it suffered from inefficiency, bureaucracy and over-staffing. In January 2004, Maria Ramos took over as the Chief Executive of the Transnet group. She implemented a four-point turnaround strategy for the revival of Transnet. This book details how she transformed the operations of the company.
Originally Published in: Nussbaum, B., & Mosala, T. (2009). Maria Ramos: Transforming Transnet Strategy. WBS-2009-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Transnet (Firm : South Africa); Transportation -- Management -- Case studies; Corporate turnarounds -- Case studies